1985
DOI: 10.1200/jco.1985.3.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Extended versus involved fields irradiation combined with MOPP chemotherapy in early clinical stages of Hodgkin's disease.

Abstract: From 1976 to 1981, 335 patients with untreated Hodgkin's disease, clinical stages I, II, and IIIA, have been treated by MOPP (nitrogen mustard, vincristine, procarbazine, prednisone) chemotherapy, three to six cycles according to the prognostic factors, combined with radiotherapy. Irradiation was always performed after the first three cycles of chemotherapy, and was randomized between extensive radiotherapy, ie, mantle and paraaortic areas for supradiaphragmatic presentations, and radiotherapy restricted to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

1987
1987
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(31 citation statements)
references
References 17 publications
1
28
0
2
Order By: Relevance
“…The Pierre et Marie Curie study group (17) showed that classical blanket irradiation can be replaced by fields limited to the site previously involved by the disease -involvedfield radiation, believing that chemotherapy will adequately treat the microscopic disease of macroscopically uninvolved areas. These findings were later confirmed by other authors (10,18,19) and the combined modality of chemotherapy plus involved-field radiotherapy has become the goldstandard treatment for low-risk HL, even for those with unfavorable risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The Pierre et Marie Curie study group (17) showed that classical blanket irradiation can be replaced by fields limited to the site previously involved by the disease -involvedfield radiation, believing that chemotherapy will adequately treat the microscopic disease of macroscopically uninvolved areas. These findings were later confirmed by other authors (10,18,19) and the combined modality of chemotherapy plus involved-field radiotherapy has become the goldstandard treatment for low-risk HL, even for those with unfavorable risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The HD10 trial was conducted at 329 sites across 5 countries. 1 When outcomes are considered relative to those reported in other trials that have included higher-risk patients, 16,17,45,46 it is perhaps surprising that, with a median follow-up of 79 months, the 8-year FFTF associated with the recommended arm is only 86%. Although again associated with substantial risks of cross-trial comparisons, these results are, at best, similar to those described for other trials evaluating higherrisk patients.…”
Section: The Treatment Of Limited-stage Hodgkin Lymphoma: a Hematologmentioning
confidence: 99%
“…A non-randomized study from Stanford argues that TNI yields similar results with combination therapy in patients with moderate, general symptoms who demonstrate no other unfavorable signs (26). Studying the effects of radiotherapy volumes combined with chemotherapy reveals no differences in relapsefree survival nor overall survival: approximately Yo"/;) of the patients live relapse-free (27).…”
Section: Rudiotherupymentioning
confidence: 99%